Pulmonary Vein Stenosis-Evolving Surgical Management of a Challenging Disease - Eric N. Feins; Ryan Callahan; Christopher W. Baird (MDPI AG, 2021)
Pulmonary vein stenosis (PVS) is an extremely challenging clinical problem in congenital heart disease. It has traditionally required multimodal therapy given its complex underlying pathophysiology. As with other modalities, surgical therapy has undergone tremendous evolution since the 1950s. These evolving strategies have been based upon an improved understanding of the substrates that cause PVS and recurrent vein obstruction. More recent anatomic-based surgical strategies have focused on the pulmonary vein course, and how adjacent mediastinal structures can create a fulcrum effect on the pulmonary veins as they pass from the lung parenchyma to the left atrium. The consequent angulation of pulmonary veins creates altered wall shear stress and likely serves as a nidus for recurrent PVS. Encouraging early results suggest that eliminating pulmonary vein angulation and shortening/straightening the pulmonary vein course may prove effective in surgically managing PVS.